The Influence of Asset inventory, Quality of Human Resources and Leadership Commitment to Optimization of Asset Management and Quality of Financial Statements Regional Government of Taliabu Island Regency - Irwan Mansyur (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The purpose of this study was to analyze the effect of asset inventory, quality of humanresources and leadership commitment to the quality of financial statements byoptimizing assets as a mediating variable. This research was conducted at SKPDwithin the scope of Taliabu district government with a focus of research on the Headof SKPD, Head of Planning and SKPD Asset Management at 39 SKPD and RegionalAsset Management Field with 117 samples and the sampling method is the censusmethod. Data sources using questionnaires and data analysis techniques used are thePartial Least Square (PLS) approach using Smart PLS 3.0 software. The resultsshowed that asset inventory and leadership commitment had a significant effect onasset optimization, but the quality of human resources had no significant effect. Inaddition, asset inventory, quality of human resources, leadership commitmentsignificantly influences the quality of financial statements and have a significant effectthrough asset optimization.